Association of SLCO1B1 gene variants with angiotensin-converting enzyme inhibitor-induced cough in a Pakistani hypertensive cohort - Arooj Fatima Sheikh; Nayla Munawar; Rukhsana Nawaz; Hizbullah Khan; Hizbullah Khan; Mehwish Rafique; Faryal Jahan; Sagheer Ahmed (Frontiers Media S.A., 2024)
BackgroundAngiotensin-converting enzyme inhibitors (ACEIs) are prescribed for individuals with high cardiovascular (CV) risk; however, persistent cough limits the use of ACEIs in a large number of patients. The current study aimed to identify the genetic variants in the SLCO1B1 gene that might be associated with ACEI-related cough in a Pakistani hypertensive population.MethodsA prospective cohort study was conducted at a tertiary care hospital in Pakistan. A total of 74 patients who had been treated with ACEIs were recruited through a convenient sampling method. The study was approved by the Institutional Review Board & Ethics Committee of the Shifa International Hospital, Islamabad. Patients provided 2 ml of blood for sequencing after signing informed consent. Partial gene sequencing of SLCO1B1 was carried out to find single nucleotide polymorphisms (SNPs) and haplotypes.ResultsIt was found, through a structured questionnaire, that thirty-eight (38) patients experienced cough within 2 weeks of ACEI administration and were considered as a case group (cough), and thirty-six (36) patients were considered as a control group (no cough). The incidence of cough was 51%. We found six different SNPs and 9 haplotypes in the partial gene sequences of SLCO1B1. Haplotype H4 was associated significantly with cough after adjusting for sex and smoking status. Other SNPs and haplotypes were not significantly associated with ACE-Is-induced cough.ConclusionThese findings emphasize the significance of SLCO1B1 genetic variants, specifically H4, as a potential predictor of ACEI-induced cough. It could be included in clinical practice as a possible risk factor for ACEI-induced cough once confirmed in larger clinical trials with bigger sample sizes. The replication of these findings in larger and more diverse populations is likely to contribute to the therapeutic use of ACEIs by predicting ACEI-induced cough.